2013
DOI: 10.1097/01.naj.0000431911.65473.35
|View full text |Cite
|
Sign up to set email alerts
|

Managing Irritable Bowel Syndrome

Abstract: OVERVIEW Irritable bowel syndrome (IBS), characterized by abdominal pain or discomfort associated with a change in bowel patterns, is one of the most common functional gastrointestinal disorders. Because no single drug effectively relieves all IBS symptoms, management relies on dietary and lifestyle modifications, as well as pharmacologic and nonpharmacologic therapies. The authors review current approaches to treatment and discuss nursing implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 90 publications
0
21
0
3
Order By: Relevance
“…Tegaserod is a 5-HT type 4 receptor partial agonist. The drug was initially approved by the FDA in 2002 for the treatment of IBS-C in women.In clinical trials, it was shown to be superior to placebo in improving global IBS symptoms, but it was withdrawn from the market in 2007 because of an increased risk of cardiovascular events 61 . Prucalopride is a very highly selective 5-HT type 4 receptor agonist.…”
Section: Serotonin Receptor Agonists and Antagonistsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tegaserod is a 5-HT type 4 receptor partial agonist. The drug was initially approved by the FDA in 2002 for the treatment of IBS-C in women.In clinical trials, it was shown to be superior to placebo in improving global IBS symptoms, but it was withdrawn from the market in 2007 because of an increased risk of cardiovascular events 61 . Prucalopride is a very highly selective 5-HT type 4 receptor agonist.…”
Section: Serotonin Receptor Agonists and Antagonistsmentioning
confidence: 99%
“…They're often the first line of defense before stimulant or other types of laxatives are used. There is also less risk of cramping or explosive diarrhoea that occurs with stimulant laxatives 61 . A stimulant laxative is recommended in patients that have neat, soft stools which are hard to pass.…”
Section: Laxativesmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition is characterized by recurrent episodes of functional gastrointestinal symptoms not caused by anatomical abnormalities or inflammation. The pathophysiological mechanisms related to IBS are not clearly understood [4] and are thought to result from a combination of visceral hypersensitivity, changes in gut microbiota, and altered gastrointestinal motility [5]. …”
Section: Introductionmentioning
confidence: 99%